Differential effects of GABA in modulating nociceptive vs. non-nociceptive synapses. (9th July 2015) - Wang, Y.; Summers, T.; Peterson, W.; Miiller, E.; Burrell, B.D.
Highlights: GABA differentially modulates distinct synaptic inputs under physiological conditions. GABA inhibited non-nociceptive synapses, but excited nociceptive synapses. The excitatory effect of GABA was dependent on the activity of the Cl − importer. The inhibitory effect of GABA was dependent on the activity of the Cl − exporter. Differences in Cl − gradient were functionally/behaviorally relevant. Abstract: GABA (γ-amino-butyric acid) -mediated signaling is normally associated with synaptic inhibition due to ionotropic GABA receptors that gate an inward Cl − current, hyperpolarizing the membrane potential. However, there are also situations where ionotropic GABA receptors trigger a Cl − efflux that results in depolarization. The well-characterized central nervous system of the medicinal leech was used to study the functional significance of opposing effects of GABA at the synaptic circuit level. Specifically, we focused on synapses made by the nociceptive N cell and the non-nociceptive P (pressure) cell that converge onto a common postsynaptic target. It is already known that GABA hyperpolarizes the P cell, but depolarizes the N cell and that inhibition of ionotropic GABA receptors by bicuculline (BIC) has opposing effects on the synapses made by these two inputs; enhancing P cell synaptic transmission, but depressing N cell synapses. The goal of the present study was to determine whether the opposing effects of GABA were due to differences in Cl − homeostasis between the two presynaptic neurons. VU 0240551 (VU), an inhibitor of the Cl − exporter K-Cl co-transporter isoform 2 (KCC2), attenuated GABA-mediated hyperpolarization of the non-nociceptive afferent while bumetanide (BUM), an inhibitor of the Cl − importer Na-K-Cl co-transporter isoform 1 (NKCC1), reduced GABA-mediated depolarization of the nociceptive neuron. VU treatment also enhanced P cell synaptic signaling, similar to the previously observed effects of BIC and consistent with the idea that GABA inhibits synaptic signaling at the presynaptic level. BUM treatment depressed N cell synapses, again similar to what is observed following BIC treatment and suggests that GABA has an excitatory effect on these synapses. The opposing effects of GABA could also be observed at the behavioral level with BIC and VU increasing responsiveness to non-nociceptive stimulation while BIC and BUM decreased responsiveness to nociceptive stimulation. These findings demonstrate that distinct synaptic inputs within a shared neural circuit can be differentially modulated by GABA in a functionally relevant manner.